Integrity of Adult Pig and Newborn Piglets Liver Fragments Under Different Cryopreservation Conditions - Sandomirsky, B. P.; Galchenko, S. E.; Tynynyka, L. N. (Problems of Cryobiology and Cryomedicine, 2003)
The effect of cryopreservation factors (cooling rates and cryoprotectants in different concentrations) on the integrity of newborn piglet and adult pig liver fragments was investigated. There was demonstrated the minimum damage of studied biomaterial during cryopreservation on the peroxide processes and the intensity of endogenous respiration when using polyethylene oxides (PEO-400 and PEO-1500) as cryoprotectants with 1 and 8000Â°C/min cooling rates.